2004
DOI: 10.1002/cne.11037
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐dependent regulation of the potassium channel subunits Kv1.1 and Kv3.1

Abstract: Afferent activity, especially in young animals, can have profound influences on postsynaptic neuronal structure, function and metabolic processes. Most studies evaluating activity regulation of cellular components have examined the expression of ubiquitous cellular proteins as opposed to molecules that are specialized in the neurons of interest. Here we consider the regulation of two proteins (voltage-gated potassium channel subunits Kv1.1 and Kv3.1) that auditory brainstem neurons in birds and mammals express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 74 publications
7
74
1
Order By: Relevance
“…This is in contrast to the observation by Lu et al (2004); Kv1.1 labeling in NL was predominant in the neuronal soma rather than in the neuropil, and the difference may be attributable to the different polyclonal antibody raised against Kv1.1. The neurons in NM showed a slight gradient of Kv1.2 immunoreactivity (Fig.…”
Section: Expression Of Kv1 Channels In Nlcontrasting
confidence: 99%
“…This is in contrast to the observation by Lu et al (2004); Kv1.1 labeling in NL was predominant in the neuronal soma rather than in the neuropil, and the difference may be attributable to the different polyclonal antibody raised against Kv1.1. The neurons in NM showed a slight gradient of Kv1.2 immunoreactivity (Fig.…”
Section: Expression Of Kv1 Channels In Nlcontrasting
confidence: 99%
“…Antibodies for C terminal of mouse Kv1.1 protein were obtained from Alomone Labs (APC-009). The staining pattern by this antibody was similar to that in the study by Lu et al (2004). Four posthatched chickens (P3, P8, P10, and P11) were perfused through the heart with 10% formalin-PBS, and brains were dissected out, postfixed for 2 hr in 10% formalin-PBS, and kept overnight in 30% sucrose-PBS.…”
Section: Methodssupporting
confidence: 64%
“…In rat, immunolabeling to Kv1.1 showed a gradient across the tonotopic axis in the lateral superior olive (LSO), which underlies the firing properties of principal neuron (Barnes-Davies et al, 2004). However, tonotopic gradient of Kv1.1 protein was not clearly demonstrated in the NM of the chicken (Lu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While the acoustic environment has been shown to influence auditory brain stem responses through modulation of voltage-gated potassium channels, this is achieved largely through phosphorylation rather than chronic alterations in gene expression (Chambard and Ashmore, 2005;Kaczmarek et al, 2005;Macica et al, 2003;Song et al, 2005). Studies in the avian cochlear nucleus (nucleus magnocellularis) have shown large deafness-related changes in Kv1.1 and Kv3.1 expression following cochlear ablation (Lu et al, 2004;von Hehn et al, 2004). However, these changes are transient (Lu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the avian cochlear nucleus (nucleus magnocellularis) have shown large deafness-related changes in Kv1.1 and Kv3.1 expression following cochlear ablation (Lu et al, 2004;von Hehn et al, 2004). However, these changes are transient (Lu et al, 2004). Similarly, the expression of Kv1.1 and Kv1.2 in the rat cochlear nucleus is unchanged 10 days after cochlear ablation (Caminos et al, 2005).…”
Section: Introductionmentioning
confidence: 99%